SOME PROBLEMATIC FOSSILS FROM THE VENDIAN OF THE SOUTHEASTERN WHITE SEA REGION - Ivantsov A.Yu.; Malakhovskaya Ya.E.; Serezhnikova E.A. (My University, 2004)
Three new genera and five new species of uncertain taxonomic position, i.e., Solza margarita gen. et sp. nov., Parvancorina sagitta sp. nov., Karakhtia nessovi gen. et sp. nov., Temnoxa molliuscula gen. et sp. nov., and Vaveliksia vana sp. nov., from the Late Vendian localities of the Onega Peninsula and Zimnii Bereg of the White Sea are described.
Keywords: Metazoa; Late Vendian; Arkhangelsk Region; White Sea; Russia; Precambrian::Proterozoic::Neoproterozoic::Vendian; Докембрий::Протерозой::Неопротерозойская::Вендский